Development of CRISPR/Cas9-Mediated Gene-Drive Construct Targeting the Phenotypic Gene in Plutella xylostella - Asad, Muhammad; Liu, Dan; Li, Jianwen; Chen, Jing; Yang, Guang (Frontiers in Physiology, 2022)
The gene-drive system can ensure that desirable traits are transmitted to the progeny more than the normal Mendelian segregation. The clustered regularly interspersed palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) mediated gene-drive system has been demonstrated in dipteran insect species, including Drosophila and Anopheles, not yet in other insect species. Here, we have developed a single CRISPR/Cas9-mediated gene-drive construct for Plutella xylostella, a highly-destructive lepidopteran pest of cruciferous crops. The gene-drive construct was developed containing a Cas9 gene, a marker gene (EGFP) and a gRNA sequence targeting the phenotypic marker gene (Pxyellow) and site-specifically inserted into the P. xylostella genome. This homing-based gene-drive copied ∼12 kb of a fragment containing Cas9 gene, gRNA, and EGFP gene along with their promoters to the target site. Overall, 6.67% - 12.59% gene-drive efficiency due to homology-directed repair (HDR), and 80.93% - 86.77% resistant-allele formation due to non-homologous-end joining (NHEJ) were observed. Furthermore, the transgenic progeny derived from male parents showed a higher gene-drive efficiency compared with transgenic progeny derived from female parents. This study demonstrates the feasibility of the CRISPR/Cas9-mediated gene-drive construct in P. xylostella that inherits the desired traits to the progeny. The finding of this study provides a foundation to develop an effective CRISPR/Cas9-mediated gene-drive system for pest control.